2015
DOI: 10.3389/fnbeh.2015.00175
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met and 5-HTTLPR Genotype are Each Associated with Visual Scanning Patterns of Faces in Young Children

Abstract: Previous studies have documented both neuroplasticity-related BDNF Val66Met and emotion regulation-related 5-HTTLPR polymorphisms as genetic variants that contribute to the processing of emotions from faces. More specifically, research has shown the BDNF Met allele and the 5-HTTLPR Short allele to be associated with mechanisms of negative affectivity that relate to susceptibility for psychopathology. We examined visual scanning pathways in response to angry, happy, and neutral faces in relation to BDNF Val66Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
(111 reference statements)
1
6
0
Order By: Relevance
“…Here, SNPs are selected a priori, on a theoretical basis with regard to their functions and previous findings, as evidence suggests many SNPs directly or indirectly affect neurotransmitter function and other neural mechanisms that may play a particular role in phenotypic expression. Our work, and that of others, has identified that normal genotypic variation is associated with differences in important behaviours in typically developing populations [7,8].…”
Section: Introductionsupporting
confidence: 68%
“…Here, SNPs are selected a priori, on a theoretical basis with regard to their functions and previous findings, as evidence suggests many SNPs directly or indirectly affect neurotransmitter function and other neural mechanisms that may play a particular role in phenotypic expression. Our work, and that of others, has identified that normal genotypic variation is associated with differences in important behaviours in typically developing populations [7,8].…”
Section: Introductionsupporting
confidence: 68%
“…Finally, although genetic reports were not available for the current study, future research could investigate the relationship between genetic factors and social attention. Interestingly, our previous work has demonstrated a relationship between genetic variation and visual scanning of emotional faces [43]. Overall looking time indicated good levels of task engagement by both groups, highlighting the opportunities afforded by using eye tracking to investigate the mechanisms subserving clinically relevant behaviours in males with FXS.…”
Section: Discussionmentioning
confidence: 85%
“…Viewing was binocular, but only data from the right eye were collected. All children initially participated on a short face processing eye-tracking experiment with an overall duration of 3-min (see Christou et al, 2015 ). After the completion of the first experiment, children were given a short break and were prepared to participate in the affective processing experiment.…”
Section: Methodsmentioning
confidence: 99%
“…During calibration, the EyeLink recorded the eye position and a 9-target location calibration was conducted providing the required reference data for computing gaze positions to ensure a point of fixation error rate of less than 0.5 degrees. A mini calibration was repeated every five trials in order to ensure that eye movement data were adjusted for small-scale movement of the head (see also Christou et al, 2015 ). In the case of unsatisfactory eye-tracking, a 9-point calibration was repeated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation